1994
DOI: 10.1093/jn/124.12.2344
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Is a Growth Factor for Rats as Shown by Enhanced Weight Gain and Improved Feed Efficiency ,

Abstract: We studied the effect of conjugated linoleic acid (CLA) on rat development and growth. Primigravid female Fischer rats were fed control or CLA-supplemented (0.25% or 0.5% CLA) diets during gestation and/or lactation. Conjugated linoleic acid was incorporated into milk fat and tissue lipids proportional to the level of CLA fed and the duration of CLA feeding. Conjugated linoleic acid was incorporated into fetal and neonatal tissues; it did not affect litter size nor induce apparent abnormalities. To the contrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
4
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(181 citation statements)
references
References 16 publications
11
163
4
3
Order By: Relevance
“…The failure to observe consistent changes in tissue CLA content of pigs sampled at birth leads one to question whether there is placental transfer. Heart, kidney, and adipose tissues did show changes in fatty acids but these patterns were not similar to those previously described in other animal models [7]. CLA accretion was observed in the kidneys and hearts of newborn pigs from CLA fed sow's indicating CLA did transfer across the placenta to fetal tissues.…”
Section: Resultscontrasting
confidence: 62%
“…The failure to observe consistent changes in tissue CLA content of pigs sampled at birth leads one to question whether there is placental transfer. Heart, kidney, and adipose tissues did show changes in fatty acids but these patterns were not similar to those previously described in other animal models [7]. CLA accretion was observed in the kidneys and hearts of newborn pigs from CLA fed sow's indicating CLA did transfer across the placenta to fetal tissues.…”
Section: Resultscontrasting
confidence: 62%
“…Yuan et al (2009b) showed that diet supplemented with 1.0% conjugated linolenic acid (CLnA) isomers (α-eleostearic and/or punicic acid) fed for 6 weeks did not significantly affect the body mass of mice. In contrast, Chin et al (1994) reported that conjugated linoleic acid (CLA) is a dietary factor enhancing rats growth. In the study of Arao et al (2004) with obese, hyperlipidaemic Otsuka LongEvans Tokushima Fatty (OLETF) rats, dietary PSO reduced weight of omental white adipose tissues, but not that of abdominal white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…CLA supplementation during gestation and lactation elicits greater body weight and feed efficiency in weanling mice relative to control animals 22 . This effect on feed efficiency and growth seems to be exerted by the cis-9,trans-11 isomer 4 .…”
Section: Evidence Of Conjugated Linoleic Acid Effects On Body Weight mentioning
confidence: 93%